MODEL SUPPLY CHAIN MANAGEMENT DALAM MENINGKATAKAN KINERJA PT XYZ (KAB. BEKASI) - Anggun Maradika; Didin Hikmah Perkasa (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine and investigate the effect of the Supply Chain Management Model in improving the performance of PT XYZ. This research design uses quantitative methods with data collection through questionnaires. The population in the study amounted to 112 employees of PT XYZ, and a sample of 112 people. the research was conducted by census. The collected data were analysed using Partial Least Squares Structural Equation Modeling (Smart- PLS). The main findings show that Relationship with suppliers has a positive and significant influence on Company performance. The statistical analysis results show a significant t-statistic value (3.970) and a p-value that is less than 0.05 so it can be concluded that the first hypothesis (H1) is accepted. Relationships with customers have a positive influence on Company performance. The results of statistical analysis show a significant t-statistic value (0.391) and a p-value of less than 0.698 greater than 0.5 so it can be concluded that the second hypothesis (H2) is rejected, meaning that in this study Relationship with Customers has a positive but insignificant effect on Company Performance. Furthermore, the level of information sharing has a positive and significant effect on company performance. The results of statistical analysis show a significant t-statistic value (4.849) and a p-value of less than 0.0000 smaller than 0.05 so it can be concluded that the third hypothesis (H3) is accepted